A Search for the Protonation Model with Thermodynamic Dissociation Constants and (Extra)-Thermodynamics of Nilotinib Hydrochloride (TASIGNA) - Meloun, Milan; Pilařová, Lucie; Javůrek, Milan; Pekarek, Tomáš (Springer, 2019)
Nilotinib hydrochloride (AMN107, TASIGNA, Novartis) is used to treat adults with chronic myeloid leukemia (CML), a type of leukemia. It is a novel, orally active BCR-ABL tyrosine kinase inhibitor derived from aminopyrimidine that is 30 times more effective against CML cells than is Imatinib. The nonlinear regression of the A versus pH spectra with REACTLAB and SQUAD84 and of the pH-titration curve with ESAB determined the four close and consecutive dissociation constants in the 11 steps of the newly proposed procedure. Prediction of pK(a) performed by MARVIN, PALLAS and ACD/Percepta determined the protonation sites. The sparingly soluble nilotinib hydrochloride denoted as L forms four water-soluble LH+, LH22+, LH33+, and LH44+ cations. Although the adjusted pH has less effect on the absorbance changes in the chromophore, four thermodynamic dissociation constants were reliably determined: pKa1T=3.600.04, pKa2T=4.42 +/- 0.07, pKa3T=4.71 +/- 0.04, and pKa4T=4.84 +/- 0.03 at 25 degrees C and pKa1T=3.61 +/- 0.11, pKa2T=4.29 +/- 0.18, pKa3T=4.49 +/- 0.02, and pKa4T=5.05 +/- 0.03 at 37 degrees C, and by regression analysis of potentiometric titration curves with ESAB, pKa1T=3.74 +/- 0.01, pKa2T=4.05 +/- 0.01, pKa3T=4.25 +/- 0.01, and pKa4T=4.91 +/- 0.20 at 25 degrees C and pKa1T=3.63 +/- 0.03, pKa2T=3.96 +/- 0.03, pKa3T=4.18 +/- 0.03, and pK41T=4.81 +/- 0.05 at 37 degrees C. Positive enthalpy values H degrees at 25 degrees C showed that the dissociation process is endothermic and is accompanied by heat absorption. Inasmuch as the entropy values of the dissociation process S degrees at 25 degrees C and 37 degrees C were negative, the dissociation process is reversible.
Hledání protonačního modelu s termodynamikou disociační konstantou a (extra)-termodynamika hydrochloridu Nilotinibu (TASIGNA)
Keywords: Dissociation constants; Nilotinib; Spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB; Disociační konstanty; Nilotinib; Spektrofotometrická titrace; pH-titrace; REACTLAB; SQUAD84; ESAB